Land use leverage points to reduce GHG emissions in U.S. agricultural supply chains. (14th October 2021) - Pelton, Rylie E O; Spawn-Lee, Seth A; Lark, Tyler J; Kim, Taegon; Springer, Nathaniel; Hawthorne, Peter; Ray, Deepak K; Schmitt, Jennifer
Abstract: Recognizing the substantial threats climate change poses to agricultural supply chains, companies around the world are committing to reducing greenhouse gas (GHG) emissions. Recent modeling advances have increased the transparency of meat and ethanol industry supply chains, where conventional production practices and associated environmental impacts have been characterized and linked to downstream points of demand. Yet, to date, information and efforts have neglected both the spatial variability of production impacts and land use changes (LUCs) across highly heterogeneous agricultural landscapes. Developing effective mitigation programs and policies requires understanding these spatially-explicit hotspots for targeting GHG mitigation efforts and the links to downstream supply chain actors. Here we integrate, for the first time, spatial estimates of county-scale production practices and observations of direct LUC into company and industry-specific supply chains of beef, pork, chicken, ethanol, soy oil and wheat flour in the U.S., thereby conceptually changing our understanding of the sources, magnitudes and influencers of agricultural GHG emissions. We find that accounting for LUC can increase estimated feedstock emissions per unit of production by a factor of 2- to 5-times that of traditionally used estimates. Substantial variation across companies, sectors, and production regions reveal key opportunities to improve GHG footprints by reducing land conversion within their supply chains.